1994
DOI: 10.1002/ajmg.1320530412
|View full text |Cite
|
Sign up to set email alerts
|

Small terminal deletions of the long arm of chromosome 2: Two new cases

Abstract: We report on 2 girls with small de novo terminal deletions of the long arm of chromosome 2 and breakpoints within q37. Four cases with similar or more extensive deletions have been previously reported in full. Hypotonia and psychomotor retardation were the only manifestations common to all 6 cases. The phenotype associated with small terminal 2q deletions is variable and clearly not always as mild as indicated in previous reports. The abnormality may also be more common than has been assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 9 publications
4
26
0
Order By: Relevance
“…The most frequent mechanism of ring formation involves one break in each arm followed by fusion, resulting in loss of genetic material of the distal segments of the chromosome involved. Wassink et al [2005] reported 3 cases with autism spectrum disorders and chromosome 2q37.3 terminal deletions and concluded that the 2q37.3 region continues to be a region of interest for autism susceptibility, a statement in agreement with several similar cases [Fisher et al, 1994;Phelan et al, 1995;Ghaziuddin and Burmeister, 1999;Aldred et al, 2004;Casas et al, 2004;Lukusa et al, 2004;Williams et al, 2010].…”
Section: Discussionsupporting
confidence: 54%
“…The most frequent mechanism of ring formation involves one break in each arm followed by fusion, resulting in loss of genetic material of the distal segments of the chromosome involved. Wassink et al [2005] reported 3 cases with autism spectrum disorders and chromosome 2q37.3 terminal deletions and concluded that the 2q37.3 region continues to be a region of interest for autism susceptibility, a statement in agreement with several similar cases [Fisher et al, 1994;Phelan et al, 1995;Ghaziuddin and Burmeister, 1999;Aldred et al, 2004;Casas et al, 2004;Lukusa et al, 2004;Williams et al, 2010].…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, an imprinting effect is unlikely to play a role in this deletion. Nineteen cases did not present with AHO findings [Coldwell et al, 1992;Conrad et al, 1995;Fisher et al, 1994;Friedman et al, 1997;Gorski et al, 1989;Haag et al, 1993;Lamb et al, 1990;Lin et al, 1992;Mascarello and Hubbard, 1991;Stein et al, 1992;Stratton et al, 1994;Wang et al, 1994;present study]. Most (10) are below the age of 5 years except for one 11 and one 44-year-old patient.…”
Section: Discussionmentioning
confidence: 97%
“…Thirty-three cases of deletion of chromosome band 2q37 as the sole abnormality have been reported [Coldwell et al, 1992;Conrad et al, 1995;Fisher et al, 1994;Friedman et al, 1997;Gorski et al, 1989;Haag et al, 1993;Lamb et al, 1990;Lin et al, 1992;Mascarello and Hubbard, 1991;Phelan et al, 1995;Powers et al, 1997;Stein et al, 1992;Stratton et al, 1994;VoitSzoboszlai et al, 1998;Wang et al, 1994;Wilson et al, 1995]. Of these, three cases involve a deletion of the sub-band 2q37.3 and in one case it is either 2q37.2 or 2q37.3 [Phelan et al, 1995, and the present report].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoplastic nipples are found only in three patients with a deletion involving 2q24 (Fryns et aL, 1977;McConnell et aL, 1980;Shabtai et al, 1982). The phenotype of distal 2q deletions is mild and apparently distinct from that of medial 2q deletion (Fisher et al, 1994). Few cases of proximal 2q deletions have been reported with more severe internal malformations (Antich et aL, 1981;Fryns et al, 1977).…”
Section: Discussionmentioning
confidence: 98%